2014
DOI: 10.1007/978-3-662-44774-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analysis of Denial-of-Service Attacks in the Bitcoin Ecosystem

Abstract: Abstract. We present an empirical investigation into the prevalence and impact of distributed denial-of-service (DDoS) attacks on operators in the Bitcoin economy. To that end, we gather and analyze posts mentioning "DDoS" on the popular Bitcoin forum bitcointalk.org. Starting from around 3 000 different posts made between May 2011 and October 2013, we document 142 unique DDoS attacks on 40 Bitcoin services. We find that 7% of all known operators have been attacked, but that currency exchanges, mining pools, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(98 citation statements)
references
References 10 publications
2
88
0
Order By: Relevance
“…This finding is intuitive because each pool battles for the reward; and eliminating the largest mining pool has the greatest impact on the chances of the remaining mining pools to win. It is also consistent with what has been observed empirically: 63% of large mining pools have experienced DDoS attacks, compared to just 17% of small ones [6]. Second, we observed that the larger mining pool has a slightly greater incentive to attack than the smaller mining pool.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is intuitive because each pool battles for the reward; and eliminating the largest mining pool has the greatest impact on the chances of the remaining mining pools to win. It is also consistent with what has been observed empirically: 63% of large mining pools have experienced DDoS attacks, compared to just 17% of small ones [6]. Second, we observed that the larger mining pool has a slightly greater incentive to attack than the smaller mining pool.…”
Section: Discussionsupporting
confidence: 92%
“…2 Mining pools have been sporadically targeted by DDoS attacks since 2011. According to an empirical analysis of Bitcoin-related DDoS attacks [6], mining pools are the second-most frequently targeted Bitcoin service after currency exchanges. Of 49 mining pools, 12 experienced DDoS attacks, often repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…The http-flooding assault exchanges a vast sum of hypertext parcels towards a focused on attendant to reason the foreswearing of administration. Meanwhile the bitcoin benefit necessity is constantly given to the clients, cure all to DDoS assaults remain required [34]. 3.9.1 51% Attack Now a bitcoin situation, a 51% assault changes along with distorts 51% about the records all the while.…”
Section: Safety Incidentsmentioning
confidence: 99%
“…The study of available literature indicates that authors of different publications focused primarily on the idea behind the inception of bitcoin and matters of definition (Selgin, 2015;Yermack, 2013;European Central Bank, 2012;International Monetary Fund, 2016), the technical aspects of the bitcoin system (Courtois, Grajek, Naik, 2014;Vasek, Thornton, Moore, 2014;Ober, Katzenbeisser, Hamacher, 2013), the analysis of the investment behaviour of cryptocurrency users (Baek & Elbeck, 2015) and the identification of factors determining the bitcoin exchange rate (Kristoufek, 2015;Li & Wang, 2016;Polasik, Piotrowska, Wiśniewski, Kotkowski, Lightfoot, 2015). The author observed that the potential use of bitcoin in payments, which was at the foundation of the bitcoin idea, has not been sufficiently examined in research and literature on the subject.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%